KESESUAIAN RENCANA PELAKSANAAN PEMBELAJARAN DAN PROSES PEMBELAJARAN - Poppy Anggraeni; Aulia Akbar (Universitas Syiah Kuala, 2018)
Lesson plan is one of important role in the teaching and learning process in Primary Schools. It contains plans for activities or activities that will be carried out during learning. This research aims is to describe the suitability of lesson plan and the learning process in elementary school. The research method used is a survey method, involving a sample of 12 public and private elementary schools in the city of Sumedang. Data collection techniques using observation, documentation and questionnaire techniques, the data that has been obtained is then analyzed using simple statistical techniques. The results showed that the suitability of lesson plan and the learning process had a percentage of 68.0% and were in the high category. This shows that all activities listed in the lesson plan start from the initial activities (79.8%), main activities (63.8%) and closing activities (68.86%) are in accordance with the activities carried out in the learning process. Thus it can be concluded that the lesson plan that has been prepared by the teacher and the learning process that has been carried out in the Sumedang City Primary School has a high level of suitability. However, even though it has a high category, but not fully in accordance with the lesson plan used, so there is still a need for further guidance and development for teachers so that they are always guided by the lesson plan so that learning becomes more directed and in accordance with the prepared plan.